In vitro cytotoxicity of four calcium silicate-based endodontic cements on human monocytes, a colorimetric MTT assay - Khedmat, Sedigheh (The Korean Academy of Conservative Dentistry, 2014)
OBJECTIVES: This study was performed to evaluate the cytotoxicity of four calcium silicate-based endodontic cements at different storage times after mixing. MATERIALS AND METHODS: Capillary tubes were filled with Biodentine (Septodont), Calcium Enriched Mixture (CEM cement, BioniqueDent), Tech Biosealer Endo (Tech Biosealer) and ProRoot MTA (Dentsply Tulsa Dental). Empty tubes and tubes containing Dycal were used as negative and positive control groups respectively. Filled capillary tubes were kept in 0.2 mL microtubes and incubated at 37℃. Each material was divided into 3 groups for testing at intervals of 24 hr, 7 day and 28 day after mixing. Human monocytes were isolated from peripheral blood mononuclear cells and cocultered with 24 hr, 7 day and 28 day samples of different materials for 24 and 48 hr. Cell viability was evaluated using an MTT assay. RESULTS: In all groups, the viability of monocytes significantly improved with increasing storage time regardless of the incubation time (p < 0.001). After 24 hr of incubation, there was no significant difference between the materials regarding monocyte viability. However, at 48 hr of incubation, ProRoot MTA and Biodentine were less cytotoxic than CEM cement and Biosealer (p < 0.01). CONCLUSIONS: Biodentine and ProRoot MTA had similar biocompatibility. Mixing ProRoot MTA with PBS in place of distilled water had no effect on its biocompatibility. Biosealer and CEM cement after 48 hr of incubation were significantly more cytotoxic to on monocyte cells compared to ProRoot MTA and Biodentine.